PENINGKATAN KUALITAS HIDUP LANSIA MELALUI PENERAPAN POLA HIDUP SEHAT DI PERUM OMA INDAH DESA GODOG KARANGPAWITAN GARUT - Gin Gin Sugih Permana; Aceng Ali Awaludin; Eva Daniati (LP4M STIKes Karsa Husada Garut, 2023)
Introduction: Old age (elderly) is a period that people will experience eventually. Many people can enjoy old age, but a few also experience illness and die without being able to enjoy old age happily. Objective: to provide information about healthy behavior in living life in old age so that it is always healthy and quality. Methods: This community service uses extension techniques with several stages of activities, namely the planning stage of activities to be carried out by identifying needs, identifying existing potentials and weaknesses, determining solutions and activities to be carried out, and organizing activities and the implementation stage of service activities in the form of solutions that have been approved by the local RW head. Results: This service activity results in improving the quality of elderly health by maintaining diet, sleep patterns and exercising so that the health of the elderly is maintained. Conclusion: The implementation of this community service activity received a good response from the community, especially the Perum Oma Indah community in Godog Village, Karangpawitan Garut. From these community service activities, the knowledge of the elderly has increased and the quality of life of the elderly with clean and healthy patterns or behavior both in the environment or healthy behavior for each individual is provided with a pocket book that can be a guide for the elderly as information or knowledge in everyday life.